2013
DOI: 10.1038/ki.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

Urine haptoglobin levels predict early renal functional decline in patients with type 2 diabetes

Abstract: Diabetic nephropathy is the leading cause of end stage renal disease. The urinary albumin to creatinine ratio is used as a predictor for the development of nephropathy but it is neither sensitive nor specific. Here we used liquid chromatography/mass spectrometry on urine of eight normoalbuminuric patients with type 2 diabetes from the VA Diabetes Trial to identify candidate markers for loss of renal function. Initial verification of 7 markers (agrin, haptoglobin, mannan-binding lectin serine protease 2, LAMP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 39 publications
3
51
0
1
Order By: Relevance
“…The accumulation of reactive oxygen species produced by activated neutrophils and macrophages [18], the endoplasmic reticulum stress and cytoskeletal changes, cause local lipid peroxidation producing alterations in glomerular permeability, leading to development of protein leakage into the Bowman's space [19]. The urinary levels of haptoglobin are correlated with the loss of GFR prior to the development of very high albuminuria, owing to the increased glomerular permeability that allows haptoglobin in the serum to leak into the urinary space [20]. We have seen elevated plasma levels of HP in very high albuminuric patients, which might not be counteracted by an increased urinary excretion.…”
Section: Discussionmentioning
confidence: 98%
“…The accumulation of reactive oxygen species produced by activated neutrophils and macrophages [18], the endoplasmic reticulum stress and cytoskeletal changes, cause local lipid peroxidation producing alterations in glomerular permeability, leading to development of protein leakage into the Bowman's space [19]. The urinary levels of haptoglobin are correlated with the loss of GFR prior to the development of very high albuminuria, owing to the increased glomerular permeability that allows haptoglobin in the serum to leak into the urinary space [20]. We have seen elevated plasma levels of HP in very high albuminuric patients, which might not be counteracted by an increased urinary excretion.…”
Section: Discussionmentioning
confidence: 98%
“…By including the haptoglobin/ creatinine ratio to a model using the albumin/creatinine ratio to predict early decline in renal function, some investigators reported an improvement in its predictive performance. 54 Thus, it was concluded that the haptoglobin/creatinine ratio may be useful to predict patients with T2DM at risk of nephropathy prior to the onset of macroalbuminuria or reduced GFR.…”
Section: Albuminuria As the Conventional Biomarkermentioning
confidence: 99%
“…Of the seven candidate markers that were initially found, only haptoglobin was verified to be the best to predict early renal functional decline. 94 However, when compared with albuminuria, urinary haptoglobin was equivalent in predicting early decline, although the combination of both albuminuria and urinary haptoglobin improved the ability to predict decline than either biomarker alone.…”
Section: Urinary Proteomicsmentioning
confidence: 96%